Sistem Pelacakan Posisi Kapal Berbasis Mobile Android dan Web Server - Meyti Eka Apriyani; Randy Giovanny; Petrus Yhan Haris (Politeknik Negeri Batam, 2012)
Ship tracking position system using GPS (Global Potisioning System) which applied to mobile phone Android operating system and communicates with a web based can monitoring where ship position and defines the location for the purpose mapping the web interface. This application can find the coordinates and send coordinates to server application and can display the position in map.